Bright's passage : a novel - Ritter, Josh. (New York : Dial Press, 2011)
World War I veteran Henry Bright grieves over the death of his young wife while he struggles to care for their new infant and travels a fire-stricken landscape accompanied by a guardian angel and a cantankerous goat.
Keywords: World War, 1914-1918 -- Veterans -- West Virginia -- Fiction; Appalachian Region -- Social life and customs -- Fiction